The Philosopher’s Role: An Interview with Dr. Russ Shafer-Landau - McIntosh, Benjamin; Shafer-Landau, Russ (Stance: an international undergraduate philosophy journal, 2017)
Article published in Stance by McIntosh and Shafer-Landau.